The fibroblast activation protein alpha as a biomarker of pulmonary fibrosis - Lavis, Philomène; Garabet, Ani; Cardozo, Alessandra Kupper; Bondue, Benjamin (Frontiers in Medicine, 2024)
Idiopathic pulmonary fibrosis (IPF) is a rare, chronic and progressive interstitial lung disease with an average survival of about 3 years. The evolution of IPF is unpredictable, with some patients presenting a relatively stable condition with limited progression over time, while others deteriorate rapidly. Besides IPF, other interstitial lung diseases can lead to pulmonary fibrosis, and up to a third have a progressive phenotype with the same prognosis as IPF. Clinical, biological and radiological risk factors of progression were identified but no specific biomarkers of fibrogenesis are currently available. A recent interest for the fibroblast activation protein alpha (FAPα) has emerged. FAPα is a transmembrane serine protease with extracellular activity. It that can also be found in a soluble form, also named anti-plasmin cleaving enzyme (APCE). FAP is specifically expressed by activated fibroblasts and quinoline-based specific inhibitors (FAPI) were developed, allowing to visualize its distribution in vivo by imaging techniques. In this review, we discuss the use of FAPα as a useful biomarker for the progression of lung fibrosis, both by its assessment in human fluids and/or its detection by imaging techniques and immunohistochemistry.